S-matrix bootstrap for effective field theories: massless pions - Guerrieri, Andrea L. [UNESP]; Penedones, João; Vieira, Pedro [UNESP] (Springer Nature, 2021)
We use the numerical S-matrix bootstrap method to obtain bounds on the two leading Wilson coefficients (or low energy constants) of the chiral lagrangian controlling the low-energy dynamics of massless pions. This provides a proof of concept that the numerical S-matrix bootstrap can be used to derive non-perturbative bounds on massless EFTs in more than two spacetime dimensions.
Keywords: Chiral Lagrangians; Effective Field Theories; Scattering Amplitudes